(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2022)
The sablefish (Trichiurus lepturus) is a semi-fatty fish, with an important content of proteins, minerals and different vitamins.The objective of this study was to elaborate and evaluate the physicochemical, microbiological, sensory and texture characteristics of a sausage from sable meat (Trichiurus lepturus), with olive oil as a source of omega 3. The proximal composition was determined following the AOAC (2012) methods.The microbiological characteristics were determined according to Colombian Technical Standards 4458. Acceptability was evaluated by a panel of untrained judges, using a hedonic scale of 4 descriptors (taste, color, odor and texture). Three formulations identified as (F1), (F2), (F3) and a control sample were tested. Significant differences (p <0.05) wereobserved between F2 and F3 with respect to F1. The highest content of polyunsaturated acids (EPA) was observed in formulation F3, in the sameway it occurred for sensory properties and nutritionalcontent. The proximal content was 15.07% protein, 5.26%fat, and 10.37% carbohydrate for F3.As for the hardness characteristic, it was higher than in formulations F1 and F2. The sausages presented good microbiological and sensory quality. These values meet the standards required by the Codex Alimentarius, so that the product obtained can be considered as a new alternative to include in the human diet.